2022
DOI: 10.48550/arxiv.2203.01085
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Current-Squared Flows and ModMax Theories

Christian Ferko,
Liam Smith,
Gabriele Tartaglino-Mazzucchelli

Abstract: We show that the recently introduced ModMax theory of electrodynamics and its Born-Infeld-like generalization are related by a flow equation driven by a quadratic combination of stress-energy tensors. The operator associated to this flow is a 4d analogue of the T T deformation in two dimensions. This result generalizes the observation that the ordinary Born-Infeld Lagrangian is related to the free Maxwell theory by a current-squared flow. As in that case, we show that no analogous relationship holds in any oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 71 publications
1
12
0
Order By: Relevance
“…which is precisely the result obtained in Ref. [23] from the dimensional reduction of the four-dimensional ModMax-Born-Infeld theory [16,17,21,22].…”
Section: Indeed Commutessupporting
confidence: 87%
See 2 more Smart Citations
“…which is precisely the result obtained in Ref. [23] from the dimensional reduction of the four-dimensional ModMax-Born-Infeld theory [16,17,21,22].…”
Section: Indeed Commutessupporting
confidence: 87%
“…( 5) admits a T T -like deformation in terms of a Born-Infeld action with parameter λ. The resulting two parameter, four-dimensional action S (λ,γ) is the solution of two commuting flow-equations [20][21][22]. The flows we introduce here precisely generate, and extend, the reduction to two dimensions of the ModMax-Born-Infeld action recently obtained in Ref.…”
Section: Introductionmentioning
confidence: 52%
See 1 more Smart Citation
“…ModMax theory has been proposed as a unique conformal nonlinear electrodynamics theory, which is a marginal modification on the pure Maxwell theory [22]. We have showed that there exists a marginal T T -like operator in the form of (2.1) in [1], which reproduces the ModMax theory from a pure Maxwell theory (Also, see [23]). we showed that the ModMax as well as generalized Born-Infeld (GBI) 1 Lagrangian density fulfill the flow equations:…”
Section: Marginal T T -Like Deformation In Modmax Theorymentioning
confidence: 76%
“…For higherdimensional cases, it has been explored in [14]. For lower dimension, i.e., the one-dimensional case or ordinary quantum mechanic system, which is the main interest of present work, the T T deformation was first introduced in [15,16], see also recent developments [17][18][19][20][21][22][23][24].…”
mentioning
confidence: 99%